Front Cover: Simultaneous H2 Production and Bleaching via Solar Photoreforming of Model Dye‐polluted Wastewaters on Metal/Titania (6/2021). Issue 6 (25th February 2021) - Puga, Alberto V.; Barka, Noureddine; Imizcoz, Mikel
Abstract : The Front Cover illustrates how an anaerobic solar treatment of model textile industry effluents containing dyes might be applied for the production of waste‐derived hydrogen using metal/titania photocatalysts. As reported in the Full Paper by A. Puga et al., this method combines decontamination and valorisation of noxious aqueous pollutants in a single feasible process promoted solely by the action of sunlight. Interestingly, dye degradation efficiencies are on par with those of the unproductive aerobic analogue procedures. In the context of prospective use of earth‐abundant and inexpensive elements as co‐catalysts for the design of titania photocatalysts, the sustained H2 evolution enabled by using Cu/TiO2 upon persistent simulated sunlight irradiation is a remarkable finding. More information can be found in the Full Paper by A. Puga et al .